2011
DOI: 10.1002/lt.22302
|View full text |Cite
|
Sign up to set email alerts
|

Complement component 4d immunostaining in liver allografts of patients with de novo immune hepatitis

Abstract: De novo immune hepatitis (DNIH) is a form of late graft dysfunction after liver transplantation. The fine mechanisms leading to the development of DNIH are not known, and whether this hepatitis is a form of rejection or a result of an auto/alloimmune injury has not been established. In our patients, DNIH was always preceded by the production of donor-specific antibodies against the glutathione S-transferase T1 (GSTT1) enzyme because of a genetic mismatch in which the donors carried the wild-type gene and the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 28 publications
3
30
0
1
Order By: Relevance
“…Consequently, it is reasonable to hypothesize that, given the nature of the procedure, DDLT recipients may be more sensitive to the detrimental effects of HLA antibodies in comparison to LDLT recipients. That said, similar to recent reports, DSA is likely to have an impact in both donor settings because our multivariate analysis demonstrated an independent association between DSA and graft failure regardless of donor type (5)(6)(7)(8)10,(19)(20)(21).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consequently, it is reasonable to hypothesize that, given the nature of the procedure, DDLT recipients may be more sensitive to the detrimental effects of HLA antibodies in comparison to LDLT recipients. That said, similar to recent reports, DSA is likely to have an impact in both donor settings because our multivariate analysis demonstrated an independent association between DSA and graft failure regardless of donor type (5)(6)(7)(8)10,(19)(20)(21).…”
Section: Discussionsupporting
confidence: 91%
“…Not until the recent seminal work of multiple investigators has the interest in alloantibodies in LT become reinvigorated (6,7,10,20,26,27). Significant associations have been made between preformed and de novo DSA and liver transplant rejection, alloimmune hepatitis and patient and graft survival (4)(5)(6)(7)(8)(9)(10)19,21,26). Still, controversy exists because some reports have refuted these findings (27), and the current data have emanated mainly from singlecenter studies.…”
Section: Discussionmentioning
confidence: 99%
“…We have not demonstrated portal venule staining or terminal hepatic venule staining with any significant frequency in native or allograft liver tissues with the fresh-frozen IF technique. This is consistent with the results of Aguilera et al 1 (see their Table 2), who found that biopsy samples from patients with non-de novo immune hepatitis did not demonstrate C4d in portal areas. We have found that IF staining for C4d is similar to the staining demonstrated by Aguilera et al in their chronic rejection group (see their Fig.…”
Section: To the Editorssupporting
confidence: 93%
“…We read the article by Aguilera et al 1 and the accompanying editorial by Bellamy 2 with great interest. As Bellamy indicates, our group has documented complement component 4d (C4d) staining in ABO-compatible liver allograft recipients in 2 recent publications.…”
Section: To the Editorsmentioning
confidence: 99%
“…Portal vein and capillary C4d deposits can also be detected in other circumstances, including biliary obstruction [98], recurrent HBV infection [99], recurrent HCV infection [101], and de novo AIH [107]. C4d staining has also been described in portal venous and capillary, sinusoidal, central vein, and arterial endothelial cells, in lymphoid nodules, and in periductal and portal stromal cells in native pediatric livers with HBV, HCV, AIH, and overlap syndromes between AIH and PSC [108].…”
Section: Histopathologic Findingsmentioning
confidence: 99%